Are acute player workloads associated with in-game performance in basketball? - L. Fox, Jordan; Stanton, Robert; J. O’Grady, Cody; Teramoto, Masaru; Sargent, Charli; T. Scanlan, Aaron (Biology of Sport, 2022)
To investigate associations between acute workload and in-game performance in basketball. Eight semi-professional, male basketball players were monitored during all training sessions (N = 28) and games (N = 18) across the season. External workload was determined using absolute (arbitrary units[AU]) and relative (AU·min-1) PlayerLoadTM (PL), and absolute (count) and relative (count·min-1) low-intensity, mediumintensity, high-intensity, and total Inertial Movement Analysis (IMA) events (accelerations, decelerations, changesof-direction, and jumps). Internal workload was determined using absolute and relative Summated-Heart-RateZones workload, session-rating of perceived exertion, rating of perceived exertion, and time (min) spent working > 90% of maximal heart rate. In-game performance was indicated by the player efficiency statistic. Repeated measures correlations were used to determine associations between acute workload variables (across the previous 7 days) and player efficiency. Relative PL (r = 0.13, small) and high-intensity IMA events (r = 0.13, small) possessed the strongest associations with player efficiency of the investigated workload variables (P > 0.05). All other associations were trivial in magnitude (P > 0.05). Given the trivial-small associations between all external and internal workload variables and player efficiency, basketball practitioners should not rely solely on monitoring acute workloads to determine performance potential in players.